Rho-GTPase activating protein 18: a biomarker associated with good prognosis in invasive breast cancer - Aleskandarany, Mohammed A.; Sonbul, Sultan N.; Surridge, Rachel; Mukherjee, Abhik; Caldas, Carlos; Diez-Rodriguez, Maria; Ashankyty, I.; Albrahim, Khalil I.; Elmouna, Ahmed M.; Aneja, Ritu; Martin, Stewart G.; Ellis, Ian O.; et al. (Cancer Research UK, 2017)
Background: The prognostic value of lymphovascular invasion (LVI) in breast cancer (BC) has been demonstrated in several independent studies. However, identification of driver molecules for LVI remains a challenging task. Large-scale transcriptomic profiling of histologically validated LVI can potentially identify genes that regulate LVI. Methods:Integrative bio-informatics analyses of the METABRIC study were performed utilising a subset of strictly defined LVI using histological and immunohistochemical (IHC) criteria. ARHGAP18 was amongst the top differentially expressed genes between LVI+ and LVI- BC with a 1.8 fold change. The prognostic impact of ARHGAP18 gene expression was assessed in the METABRIC dataset (n=1980) and externally validated using the online BC gene expression datasets utilising bc-GenExMiner v4.0 (n=2016). Subsequently, ARHGAP18 protein expression was assessed on a large cohort of invasive BC (n=959) with long term follow-up using IHC. Results: Pooled analysis of ARHGAP18 mRNA expression showed that overexpression was associated with better outcome (p<0.001, Hazard ratio (HR) =0.82, 95%CI 0.75-0.90). ARHGAP18 protein was expressed in the cytoplasm and nuclei of the tumour cells and its expression was positively associated with good prognostic variables. Lack of cytoplasmic expression showed associations with LVI (p=0.006), epithelialmesenchymal transition and the HER+ subtype (p=0.01). Loss of nuclear expression was associated higher grade, HER2+ and high Ki67LI (p=0.001). Cytoplasmic and nuclear expression showed a positive association with improved survival independent of other variables (P =0.01, HR = 0.74, 95%CI 0.60-87). Conclusions: ARHGAP18 expression at transcriptomic and protein levels is associated with improved patients’ outcomes whose deregulation may play a role in tumour progression and the development of LVI in BC. Further assessment of its potential therapeutic value in BC is warranted.